Visual inspection with acetic acid screening use determinants: a systematic literature review - Ayu, Septi; Hadi, Ella Nurlaella (BKM Public Health and Community Medicine, 2024)
Purpose: In Indonesia, in 2022, of 36,964 cervical cancer cases, 56% ended in death due to cervical cancer. Cervical cancer can be identified at an early stage through routine examinations, allowing for more effective treatment and increasing the chances of cure. The visual inspection of acetic acid (VIA) screening has emerged as a simple, effective, and affordable option. Methods: The research method uses a systematic literature review, carried out using primary studies from PubMed, Proquest, and Google Scholar using the keywords "woman; VIA; preventing cervical cancer" published between 2019 and 2024, full text and open access articles and according to the topic. Results: 25,999 research articles were screened for eligibility, and 10 met the inclusion criteria. The coverage of the VIA screening was due to age, social norms, opinions, behavior of other people, the availability of health facilities, support from husbands, support from health workers, and economic conditions. Conclusion: Educational interventions at the community and health facilities are needed to increase VIA examination coverage. Socialization and education involving women and men are expected to help increase public participation in VIA examinations and reduce morbidity and mortality due to cervical cancer.